Crystal Damage and Surface Morphology in Industrial Diamond Wire Slicing of 300 mm Monocrystalline Silicon Wafers for Microelectronic Devices - Oberhans, Stephan; Heiß, Wolfgang; Pietsch, Georg J. (Advanced Materials Technologies, 2024)
In the semiconductor industry, thin wafers are cut from a monocrystalline silicon. The most important process step is cutting the monocrystal into a multitude of thin substrate slices, which determines the properties of the resulting wafers. Some time ago, the transition from traditional slurry-wire-slicing (S-MWS) to diamond-wire-slicing (D-MWS), which is more cost-effective and resource-efficient, took place. Unlike in the photovoltaic industry and also in the production of smaller wafer diameters of up to 200 mm, it is not possible to create a seamless transition with today's standard wafer diameters of 300 mm due to the waviness that occurs on the wafer surface immediately after the cutting process. This situation considerably limits the achievable component generation (design rule), as the strict requirements of the chip manufacturers cannot be fulfilled. Therefore, a comprehensive understanding of the process is required. A detailed comparison of the surface structure, surface topography, and fracture strength is carried out based on the three relevant crystal orientations Silicon(100), Silicon(110), and Silicon(111). In addition, some wire segments are examined. All microscopic examinations carry out on both the primary and secondary chipping faces do not provide any correlation between the microscopic surface condition and the macroscopic waviness.
CRIS-Team Scopus Importer:2025-02-04
Keywords: diamond-wire-slicing (D-MWS); material removal mechanism; multi-wire-slicing (MWS); primary and secondary chipping face; silicon